Clinical Presentation and Outcome of Cats with Circumcaval Ureters Associated with a Ureteral Obstruction. (30th September 2014) - Steinhaus, J.; Berent, A.C.; Weisse, C.; Eatroff, A.; Donovan, T.; Haddad, J.; Bagley, D.
<x xml:space="preserve">Abstract</x> Background Circumcaval ureters (CU) are a rare embryological malformation resulting in ventral displacement of the caudal vena cava, which crosses the ureter, potentially causing a ureteral stricture. Objectives To evaluate cats with obstructed CU(s) and report the presenting signs, diagnostics, treatment(s), and outcomes. Cats with obstructed CU(s) were compared to ureterally obstructed cats without CU(s). Animals 193 cats; 22 circumcaval obstructed (Group 1); 106 non‐circumcaval obstructed (Group 2); 65 non‐obstructed necropsy cases (Group 3). Methods Retrospective study, review of medical records for cats treated for benign ureteral obstructions from AMC and University of Pennsylvania between 2009 and 2013. Inclusion criteria: surgical treatment of benign ureteral obstruction, complete medical record including radiographic, ultrasonographic, biochemistry, and surgical findings. Results Seventeen percent (22/128) of obstructed cats had a CU (80% right‐sided) compared to 14% (9/65) non‐obstructed necropsy cats (89% right‐sided). Clinical presentation, radiographic findings, and creatinine were not statistically different between Groups 1 and 2. Strictures were a statistically more common (40%) cause of ureteral obstruction in Group 1 compared to Group 2 (17%) (P = .01). The MST for Groups 1 and 2 after ureteral decompression was 923 and 762 days, respectively (P = .62), with the MST for death secondary to kidney disease in both groups being >1, 442 days. Re‐obstruction was the most common complication in Group 1 (24%) occurring more commonly in ureters of cats treated with a ureteral stent(s) (44%) compared to the subcutaneous ureteral bypass (SUB) device (8%) (P = .01). Conclusions and Clinical Importance Ureteral obstructions in cats with a CU(s) have a similar outcome to those cats with a ureteral obstruction and normal ureteral anatomy. Long‐term prognosis is good for benign ureteral obstructions treated with a double pigtail stent or a SUB device. The SUB device re‐obstructed less commonly than the ureteral stent, especially when a ureteral stricture was present.